The state and development - Peter B. Evans; Patrick Heller (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Using a comparative frame that draws on the variation of developmental trajectories in Asia from Northeast Asia to China to Southeast Asia and to India, this paper explores the changing role of the state in these countries and the contributions that the analysis of the Asian state has made to general theoretical understandings of the role states can play in promoting economic and social transformation. The emergence and evolution of the concept of the "developmental state" is a central focus. The ambiguous relation between the developmental state and the politics of representation and redistribution is a second central concern. Building on region-wide comparative analysis, we examine how state structures and possibilities for state action in Asia have been shaped by geo-political context and colonial heritage. We analyse the ways in which development, defined as enhanced well-being and human flourishing, and democracy, defined as accountability to the deliberatively constructed goals of society, have been facilitated or frustrated by state structures and state action. We consider what general lessons the comparative history of the Asian state offers for development theory and policy possibilities.
Keywords: 330; state; Asia; development; democracy